KINERJA PRODUKSI DAN INCOME OVER FEED COST PEMELIHARAAN AYAM BROILER PADA KANDANG CLOSED HOUSE (STUDI KASUS SUYATNO FARM DESA BANDARDAWUNG, KECAMATAN TAWANGMANGU): PRODUCTION PERFORMANCE AND INCOME OVER FEED COST OF BROILER CHICKEN REARING IN CLOSED HOUSE SYSTEM (CASE STUDY AT SUYATNO FARM, BANDARDAWUNG, TAWANGMANGU) - Penggalih, Ratna Latip; Mulyono, Ali Mursyid Wahyu; Husein, Muhammad (Tropical Animal Science, 2025)
This study aims to determine the differences in broiler chicken performance across five rearing periods by analyzing the variables of average body weight, depletion rate, feed conversion ratio (FCR), performance index (IP), and Income Over Feed Cost (IOFC). Data collection techniques used in this research include observation and questionnaires, with the subject being the close house system at Suyatno Farm. The study produced the following: averages over five rearing periods: an average pololation 19,800 chickens, an average body weight of 1.98 kg per bird, a depletion rate of 385 birds or 1.94%, a feed conversion ratio of 1.437, a performance index (IP) is 441, and IOFC IDR 14,005. The results indicate that Period 1 had the best overall performance in terms of average final body weight 2.1 kg per bird, performance index 473, and IOFC IDR 14,660. Period 2 showed the best result in depletion rate, with 348 birds lost 1.65%. Meanwhile, the best feed conversion ratio was recorded in Period 3 with a value of 1.410.